The Future Of Hotel Housekeeping: New Trends And Modern Approaches - Thoriq , Naufal; Intiar, Septa; Jabbar, Umar Abdul; Aryaningtyas, Aurilia Triani; Aswan, Mukhamad Kholil (PT. Hafasy Dwi Nawasena, 2024)
Housekeeping plays a vital role in the hotel business, exerting a major impact on client pleasure and loyalty. In order to stay competitive, hotels must constantly adapt to changing client expectations and the impact of technological improvements on operational processes. This study examines current developments and contemporary methods in hotel cleaning, with a specific emphasis on technology advancements, sustainability efforts, and guest-centered techniques. Robotic cleaners, fueled by artificial intelligence, transform cleaning procedures, while intelligent sensors offer up-to-the-minute data for operational enhancement. Artificial intelligence optimizes operational efficiency and customizes visitor experiences, resulting in improved productivity and customer satisfaction. Hotels showcase their dedication to environmental stewardship by implementing sustainability initiatives, such as the use of eco-friendly products and the adoption of waste reduction techniques. In addition, the use of energy-efficient technology and customized services enhances the satisfaction of guests while simultaneously decreasing operational expenses. The implementation of health and safety protocols, specifically in relation to COVID-19, places utmost importance on the welfare of both staff members and visitors. Hotels may improve their operational efficiency, increase visitor pleasure, and show their dedication to sustainability and staff well-being by adopting these trends and using new approaches.